Media Accounting Games For Increasing Knowledge Tudents At Dharma Karya Senior High School - Yudhi Prasetiyo; Yeni Widiastuti; Sila Ninin Wisnantiasri; Diky Paramitha; Novita Nugraheni; Dwirini Dwirini; Shufia Zuhroh (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Increasing accounting learning in the millennial generation needs to be improved. In the era of advanced technology and the rapid development of social media as literacy in understanding new learning methods, it needs to be used so that students’ interests and talents can be channeled and improved according to future needs and preparations. The current accounting function is not only to record but also to use it. To evaluate the non-financial, social, and emotional condition of decision-makers. This is what makes accounting cannot be replaced by machines and computers. Therefore, business owners, even as young as high school, need to understand accounting so they can make the right business decisions. One way to gain a good understanding of accounting is through teaching accounting. This accounting lesson is given by explaining the basic concepts and theories of accounting, identifying simple accounting applications that have occurred in everyday life with the aim of knowing the importance of accounting records, and explaining accounting principles and cycles which are the basis for understanding accounting properly. The purpose of this research was carried out based on the results of observations made during the socialization and teaching of students to increase knowledge about learning to account with media games and increase the entrepreneurial spirit for millennials and generation Z. This observation was carried out in class XII students of SMA Dharma Karya. The results obtained are that the millennial and Z generations are currently happy with game-based learning because it makes it easier for them to absorb the substance of the learning besides that the increase in knowledge about accounting is also increasing, this is evidenced by their being more active and comprehensive in solving problems in game-based learning.